2011
DOI: 10.1038/aps.2011.142
|View full text |Cite
|
Sign up to set email alerts
|

Human vascular endothelial cells reduce sphingosylphosphorylcholine-induced smooth muscle cell contraction in co-culture system through integrin β4 and Fyn

Abstract: Aim: In vascular strips, the adjacent endothelial cells modulate the contraction of vascular smooth muscle cells (VSMCs) induced by sphingosylphosphorylcholine (SPC) through nitric oxide (NO). The aim of this study was to elucidate the mechanisms by which vascular endothelial cells (VECs) reduce the SPC-induced contraction of VSMCs in a co-culture system. Methods: Human umbilical VECs and VSMCs were co-cultured. The VECs were transfected with integrin β4-or Fyn-specific siRNA. The areas of VSMCs that are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Our lab employed a HUVEC and VSMC coculture system to investigate the effect of HUVECs on VSMC contraction. We found that HUVECs could inhibit the SPC-induced VSMC contractive effect through the integrin β4/Fyn signaling pathway [55].…”
Section: Spc In Vesselsmentioning
confidence: 78%
“…Our lab employed a HUVEC and VSMC coculture system to investigate the effect of HUVECs on VSMC contraction. We found that HUVECs could inhibit the SPC-induced VSMC contractive effect through the integrin β4/Fyn signaling pathway [55].…”
Section: Spc In Vesselsmentioning
confidence: 78%
“…vSMCs typically regulate the contraction of blood vessels, and their function is finely regulated by signaling molecules sent by endothelial cells ( 30 ). The vSMC cell state is regulated by key co-transcription factors such as Klf4, Elk-1, and myocardin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SPC induces the proliferation and migration of VSMC in the nM range, an important effect that leads to the formation of a neointima in blood vessels [ 14 ]. SPC also induces the contraction of VSMC [ 54 ] and plays a major role in the pathogenesis of abnormal contraction of cerebral arteries [ 20 , 55 ]. It has been recently reported that the extent of SPC induced VSMC contraction correlates with total plasma cholesterol [ 20 ].…”
Section: Discussionmentioning
confidence: 99%